2013
DOI: 10.1007/s11368-012-0646-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 7-year application of a nitrification inhibitor, dicyandiamide (DCD), on soil microbial biomass, protease and deaminase activities, and the abundance of bacteria and archaea in pasture soils

Abstract: Purpose The nitrification inhibitor dicyandiamide (DCD) has been shown to be highly effective in reducing nitrate (NO 3 − ) leaching and nitrous oxide (N 2 O) emissions when used to treat grazed pasture soils. However, there have been few studies on the possible effects of long-term DCD use on other soil enzyme activities or the abundance of the general soil microbial communities. The objective of this study was to determine possible effects of long-term DCD use on key soil enzyme activities involved in the ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…NIs can inhibit nitrification through suppressing the activity of ammonia-oxidizing bacteria or relevant enzymes, effectively delaying the oxidization process that transforms NH 4 + into NO 3 À (Di et al, 2009;Guo et al, 2013). Maintaining a high soil NH 4 + content for a longer time by regulating the rapid conversion of soil N can effectively alleviate NO 3 À accumulation and leaching losses, in addition to reducing N 2 O emissions Fangueiro et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…NIs can inhibit nitrification through suppressing the activity of ammonia-oxidizing bacteria or relevant enzymes, effectively delaying the oxidization process that transforms NH 4 + into NO 3 À (Di et al, 2009;Guo et al, 2013). Maintaining a high soil NH 4 + content for a longer time by regulating the rapid conversion of soil N can effectively alleviate NO 3 À accumulation and leaching losses, in addition to reducing N 2 O emissions Fangueiro et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al (2013) investigated the effect of long‐term DCD application on microbial biomass, protease and deaminase activities, and the abundance of bacteria and archaea in three pasture soils. Seven years of DCD application did not affect any of the investigated factors.…”
Section: Effect Of Nis On Soil Microbesmentioning
confidence: 99%
“…Seven years of DCD application did not affect any of the investigated factors. Guo et al (2013) concluded that “the DCD nitrification inhibitor technology, therefore, appears to be an effective mitigation technology for nitrate leaching and nitrous oxide emissions in grazed pasture soils with no adverse impacts on the abundance of bacteria and archaea and key enzyme activities” .…”
Section: Effect Of Nis On Soil Microbesmentioning
confidence: 99%
“…This also did not show effects even at concentrations of 100 mg L −1 . Guo et al [12] found that after a long-term application of DCD, non-target microbes in the soil were unaffected. Therefore, the authors concluded that DCD only acts specifically on the ammonia oxidation.…”
Section: Luminescent Bacteria Testmentioning
confidence: 99%
“…This is a rather high value indicating that Piadin has hardly any toxic effect on the non-target bacterium A. fischeri. Studies testing the effect of other nitrification inhibitors such as DCD and DMPP concluded that these NIs at the recommended application rates do not affect non-target soil bacteria and act specifically on ammonia oxidation [12,36]. As A. fischeri was barely affected, this can be assumed for Piadin as well.…”
Section: Piadinmentioning
confidence: 99%